Magnetically Actuated Cell‐Robot System: Precise Control, Manipulation, and Multimode Conversion - Dai, Yuguo; Jia, Lina; Wang, Luyao; Sun, Hongyan; Ji, Yiming; Wang, Chutian; Song, Li; Liang, Shuzhang; Chen, Dixiao; Feng, Yanmin; Bai, Xue; Zhang, Deyuan; et al. (Small, 2022)
Border‐nearing microrobots with self‐propelling and navigating capabilities have promising applications in micromanipulation and bioengineering, because they can stimulate the surrounding fluid flow for object transportation. However, ensuring the biosafety of microrobots is a concurrent challenge in bioengineering applications. Here, macrophage template‐based microrobots (cell robots) that can be controlled individually or in chain‐like swarms are proposed, which can transport various objects. The cell robots are constructed using the phagocytic ability of macrophages to load nanomagnetic particles while maintaining their viability. The robots exhibit high position control accuracy and generate a flow field that can be used to transport microspheres and sperm when exposed to an external magnetic field near a wall. The cell robots can also form chain‐like swarms to transport a large object (more than 100 times the volume). This new insight into the manipulation of macrophage‐based cell robots provides a new concept by converting other biological cells into microrobots for micromanipulation in biomedical applications. Macrophage‐based cell robots are fabricated by loading nanomagnetic particles while maintaining the viability of the robot. The cell robot can be used to transport other micro‐objects or cells. In addition, the “dipole–dipole” interaction between the cell robots and the interaction of the local flow can lead them to form chain‐like swarms.